Temples of Champa in VietNam - J C Sharma (KHXH, 1992)
The book provides basic information about the Cham temples. A slightly detailed chapter on the history of Champa has beenincluded to acquaint the readers with events, circumstances and conditions prevailing during the periods in which temples were constructed